Avaliação tridimensional do lábio superior e nariz em pacientes com deformidade esquelética maxilar - Reolon, Luiza Zanette (2022)
The nasolabial region is the central aesthetic unit of the face and is a key factor in the final aesthetic perception of the orthosurgical procedure. This retrospective study evaluated the effects of maxillary dentoskeletical procedures on the nasolabial region with proper incisions, osteotomies, and sutures. The objective was evaluate which angles and linear distances must be controlled for aesthetics results. Groups were divided as: mini-implant-assisted rapid maxillary expansion (MARPE), surgically assisted rapid maxillary expansion (ERMAC), and segmented Le Fort I osteotomy (OLFIs). Cone beam computed tomography (CBCT) were used to compare preop (T0) and postop of 6 months (T1), using the Dolphin® Imaging 3D software. The statistical analysis proceeded with the Shapiro-Wilk test to verify the normality of the variables of interest, the paired t test was used for variables considered normal and Wilcoxon for the other variables. The Spearman Correlation test analyzed the presence of correlations. In the ERMAC group, the effects were widening of the lip support, widening of the nasal base region and of the PRN-SN-CBow angle. In the MARPE there was a vertical increase of the upper lip, widening of the nasal base, nasal projection. The effects of OLFIs were on superior nasal tip movement, widening of the alar base with a shortening of the columella length, increased vermilion of the upper lip, and lower slope of the commissures. Therefore, adequate incision associated with osteotomy technique and retaining sutures control the main undesired effects on nasolabial tissues.